An Eastern Association for the Surgery of Trauma multicenter trial examining prehospital procedures in penetrating trauma patients. Issue 1 (July 2021) - Taghavi, Sharven; Maher, Zoe; Goldberg, Amy J.; Chang, Grace; Mendiola, Michelle; Anderson, Christofer; Ninokawa, Scott; Tatebe, Leah C.; Maluso, Patrick; Raza, Shariq; Keating, Jane J.; Burruss, Sigrid; et al.
Abstract : BACKGROUND: Prehospital procedures (PHP) by emergency medical services (EMS) are performed regularly in penetrating trauma patients despite previous studies demonstrating no benefit. We sought to examine the influence of PHPs on outcomes in penetrating trauma patients in urban locations where transport to trauma center is not prolonged. We hypothesized that patients without PHPs would have better outcomes than those undergoing PHP. METHODS: This was an Eastern Association for the Surgery of Trauma–sponsored, multicenter, prospective, observational trial of adults (18+ years) with penetrating trauma to the torso and/or proximal extremity presenting at 25 urban trauma centers. The impact of PHPs and transport mechanism on in-hospital mortality were examined. RESULTS: Of 2, 284 patients included, 1, 386 (60.7%) underwent PHP. The patients were primarily Black (n = 1, 527, 66.9%) males (n = 1, 986, 87.5%) injured by gunshot wound (n = 1, 510, 66.0%) with 34.1% (n = 726) having New Injury Severity Score of ≥16. A total of 1, 427 patients (62.5%) were transported by Advanced Life Support EMS, 17.2% (n = 392) by private vehicle, 13.7% (n = 312) by police, and 6.7% (n = 153) by Basic Life Support EMS. Of the PHP patients, 69.1% received PHP on scene, 59.9% received PHP in route, and 29.0% received PHP both on scene and in route. Initial scene vitals differed between groups, but initial emergency department vitals did not. Receipt of ≥1 PHP increased mortality odds (odds ratio [OR], 1.36; 95% confidence interval [CI], 1.01–1.83; p = 0.04). Logistic regression showed increased mortality with each PHP, whether on scene or during transport. Subset analysis of specific PHP revealed that intubation (OR, 10.76; 95% CI, 4.02–28.78; p < 0.001), C-spine immobilization (OR, 5.80; 95% CI, 1.85–18.26; p < 0.01), and pleural decompression (OR, 3.70; 95% CI, 1.33–10.28; p = 0.01) had the highest odds of mortality after adjusting for multiple variables. CONCLUSION: Prehospital procedures in penetrating trauma patients impart no survival advantage and may be harmful in urban settings, even when performed during transport. Therefore, PHP should be forgone in lieu of immediate transport to improve patient outcomes. LEVEL OF EVIDENCE: Prognostic, level III.